Fiscal Decentralization in Indonesia: Does Discretionary Policy on Tax Facilities Remain Urgent? - Kus Pratiwi, Dian; Rahma Novikasari, Siti; Ayuningtyas Harahap, Nurmalita; Wahyuningsih, Aprillia (KnE Social Sciences, 2023)
The Regional Governments in Indonesia provide tax facilities as regulated in each region’s Head of the Region Regulations as a form of implementing fiscal decentralization. This study examined 56 Head of the Region Regulations in Indonesia on land and building tax facilities. This legal research examined the concept of tax facilities as a reflection of fiscal decentralization. In addition, it reviewed the application of discretionary power and assessed differences in Head of the Region Regulations on regional tax facilities. The result of the research demonstrated differences in the material substances of the Head of the Region Regulations on tax facilities. Those differences reflected the discretionary power that came from the Regional Tax Law. This discretion must be maintained because Heads of the Region need flexibility in managing the potential of their regions as the embodiment of regional autonomy. Keywords: Discretionary Power, Fiscal Decentralization, Regional Government, Tax Facility